2023
DOI: 10.1108/ijebr-11-2022-1012
|View full text |Cite
|
Sign up to set email alerts
|

Narratives of survival: how entrepreneurial families narrate their longevity

Abstract: PurposeThe question of crisis resistance and resilience of long-lived family businesses became particularly volatile with the beginning of the Corona crisis. In this context the project “Narratives of Survival” was launched focusing on the prevailing narratives to find out how crisis situations have been dealt with and narrated by long-lived German family firms.Design/methodology/approachBased on narrative interviews, the empirical study of transgenerational entrepreneurship was first approached in an open-end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 55 publications
(104 reference statements)
2
4
0
Order By: Relevance
“…This finding aligns with previous research highlighting firm resources and capabilities as key drivers in sustainable longevity (e.g. Boyd et al, 2023;Giner and Ruiz, 2022). However, such research has primarily relied on evolutionary theory, the RBV and organisational ecology theory principles (Habbershon and Williams, 1999;Hannan and Freeman, 1977;Nelson and Winter, 1982).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…This finding aligns with previous research highlighting firm resources and capabilities as key drivers in sustainable longevity (e.g. Boyd et al, 2023;Giner and Ruiz, 2022). However, such research has primarily relied on evolutionary theory, the RBV and organisational ecology theory principles (Habbershon and Williams, 1999;Hannan and Freeman, 1977;Nelson and Winter, 1982).…”
Section: Discussionsupporting
confidence: 88%
“…This literature has been moving from a focus on the business dynamics to a focus on the role of family interactions, goals and priorities in these organisations' transgenerational survival. This is important because recent research suggests that a family firm will survive through generations only if it understands the complexity and correctly manages its connection with the firm dynamic (Boyd et al. , 2023).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…For family businesses, the work of Boyd et al (2023) has demonstrated that three key guiding narrative principles dictate success. These focus on self-image, the relationship level and family factors, and strategy aspects of the orientation and continuation of long-lived family businesses and their families.…”
Section: Changing With the Timesmentioning
confidence: 99%